2022
DOI: 10.3390/ijms23169177
|View full text |Cite
|
Sign up to set email alerts
|

Expression of NUCB2/NESF-1 in Breast Cancer Cells

Abstract: Recently, the expression of NUCB2/NESF-1 has been linked to tumor development. We report NUCB2/NESF-1 expression and its relation to clinicopathological parameters in breast cancer cells. Immunohistochemical reactions were conducted on 446 cases of invasive ductal carcinoma (IDC) and 36 cases of mastopathy. The expression of NUCB2/NESF-1 was also examined at the mRNA and protein levels in breast cancer cell lines. A statistically significant higher level of NUCB2/NESF-1 in IDC cells was noted compared to that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…In a NUCB-2-knockout renal cancer cell line SK-RC-52, the expression levels of molecules associated with epithelial-mesenchymal transition (EMT), including E-cadherin, β-catenin, Slug and Twist, were affected by NUCB-2 suppression [ 16 ]. Another investigation found that the AMP-dependent protein kinase (AMPK)/target of rapamycin complex (mTORC) 1 signaling pathway participated in the regulation of NUCB-2-mediated metastasis and EMT [ 17 ]. FTX played an oncogenic role in LUAD and contributed to cancer development via targeting miR-335-5p/NUCB-2 axis [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a NUCB-2-knockout renal cancer cell line SK-RC-52, the expression levels of molecules associated with epithelial-mesenchymal transition (EMT), including E-cadherin, β-catenin, Slug and Twist, were affected by NUCB-2 suppression [ 16 ]. Another investigation found that the AMP-dependent protein kinase (AMPK)/target of rapamycin complex (mTORC) 1 signaling pathway participated in the regulation of NUCB-2-mediated metastasis and EMT [ 17 ]. FTX played an oncogenic role in LUAD and contributed to cancer development via targeting miR-335-5p/NUCB-2 axis [ 18 ].…”
Section: Discussionmentioning
confidence: 99%